PROBLEMATIKA YURIDIS SERTIFIKAT HAK PATEN SEBAGAI OBJEK JAMINAN FIDUSIA BERDASARKAN HUKUM POSITIF DI INDONESIA - Putu Eka Trisna Dewi; Ni Made Rai Sukardi; Dedy Suryana (Fakultas Hukum Universitas Ngurah Rai, 2026)
The development of the modern economy has increased the role of intangible assets, including patents as a form of Intellectual Property Rights (IPR) with significant economic value. Under Indonesian law, patents may normatively be used as objects of fiduciary security as regulated in Law Number 65 of 2024 concerning the Third Amendment to Law Number 13 of 2016 on Patents. This study aims to analyze the issues surrounding the utilization of patents as objects of fiduciary security based on positive law in Indonesia. The research employs a normative legal method using statutory and conceptual approaches. The results indicate that although patents legally fulfill the requirements as objects of fiduciary security, their implementation still faces several challenges, including the absence of implementing technical regulations, the lack of competent appraisal institutions for intellectual property valuation, and the low level of trust among financial institutions toward intellectual property as collateral. Therefore, more comprehensive regulations are required to provide legal certainty and optimize the utilization of patents as objects of fiduciary security.